Canva-Based Animation Comic Video Media in Informatics Learning - Liza Mustika Sari; Asrul Huda; Hansi Effendi; Muhammad Giatman (Postgraduate, University of Mataram, 2024)
This study aims to develop Canva-based animated comic video learning media that are valid, practical, and effective for Informatics in Grade VIII at SMP N 14 Padang. The research adopts a Research and Development (R&D) approach, applying the 4D model—Define, Design, Develop, and Disseminate. Primary data were collected from validators, teachers, and students, with descriptive and inferential analysis used to evaluate media validity, practicality, and effectiveness. Results show the media to be valid, scoring 0.963 for media and 0.975 for material aspects. The media is also highly practical, with teacher ratings at 97.04% and student ratings at 93.14%. Effectiveness is indicated by a Gain Score of 0.69 (medium category) and a significant improvement in student learning outcomes, as confirmed by t-test results (Sig. 2-tailed = 0.000; tcount > ttable). The findings confirm that Canva-based animated comic videos significantly enhance student learning outcomes over conventional methods.